CRITERIA AND LEVELS OF GLOBAL PROBLEMS - Axmatov Shoxrux Tuyg‘un o‘g‘li; Mustafayev Jafar Shomirzaevich (Лучшие интеллектуальные исследования, 2024)
An important feature of global problems is that they are all related to each other depends to such an extent that solving one of them at least creates other problems for him means taking into account the effect. Listed criteria of global problems and characteristic features of most researchers in this field reflects the views and differentiates global problems from all other problems, allows you to say clearly. This is the tension and importance of this or that problem to determine its level, to determine its interrelationship with other problems different classifications are usually made, they are divided into separate groups. Classification is not the only goal, but rather the extreme of the current era acts as an important element of the complex study of conflicts problems in terms of their interrelationship and mutual dependence allows learning. It is important to differentiate relationships, priorities and objective allows to determine the degree of exacerbation of existing global problems. In addition, the classification enhances the systematic interrelationship of global problems It helps to understand more deeply and the sequence of making practical decisions It helps to determine. Know the classification that is done consistently and accurately to a certain extent summarizes the previous researches in this field and at the same time notes the beginning of a new stage in the development of such research. Current between different approaches to the classification of global problems at the time especially according to the widely recognized classification of global problems, all of them the level of tension and the importance of the solution, as well as their in real life divided into three large groups depending on the causal connections between them. The first group is characterized by the greatest degree of commonality and importance problems.